2018
DOI: 10.1109/tnsre.2018.2838767
|View full text |Cite
|
Sign up to set email alerts
|

Spasticity Measurement Based on the HHT Marginal Spectrum Entropy of sEMG Using a Portable System: A Preliminary Study

Abstract: To facilitate stretch reflex onset (SRO) detection and improve accuracy and reliability of spasticity assessment in clinical settings, a new method to measure dynamic stretch reflex threshold (DSRT) based on Hilbert-Huang transform marginal spectrum entropy (HMSEN) of surface electromyography (sEMG) signals and a portable system to quantify modified Ashworth scale (MAS) for spasticity assessment were developed. The sEMG signals were divided into frames using a fixed-length sliding window, and the HMSEN of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
1
15
0
1
Order By: Relevance
“…In the three stroke patients, the activation area was different indicated that the spatial activation pattern of a spastic muscle might vary between individuals. A previous study showed that the MUs recruitment pattern resulted from the stretch reflex changed depending on the level of spasticity (Hu et al, 2018).…”
Section: The Emg Amplitude and Spatial Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the three stroke patients, the activation area was different indicated that the spatial activation pattern of a spastic muscle might vary between individuals. A previous study showed that the MUs recruitment pattern resulted from the stretch reflex changed depending on the level of spasticity (Hu et al, 2018).…”
Section: The Emg Amplitude and Spatial Distributionmentioning
confidence: 99%
“…As a complexity indicator, a small entropy value is associated with small complexity and great regularity. Studies have shown that the complexity of EMG signals changes in stroke patients with spasticity during voluntary contraction (Dash et al, 2019), and the entropy-based method can reliably and precisely detect the stretch reflex onset (Hu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanical signalbased approach has good interpretability, the absence of muscle activation analysis makes it difficult to identify the disturbance caused by contractures. In current studies, it is generally believed that TSRT [20], [21], [22] based on inertial measurement unit (IMU) and surface electromyography (sEMG) fusion exhibits reliable clinical validity. [23] shows that the neural component is the domination factor of spasticity assessment for most patients in the passive stretch test.…”
Section: Introductionmentioning
confidence: 99%
“…The stretch reflex threshold represents the joint angle at which antagonist muscles or motor neurons begin to contract when the affected limbs of the subject are stretched passively [6]. The starting point that corresponds to the beginning of contraction of antagonistic muscles or motor neurons is called stretch reflex onset [7]. Surface electromyogram (EMG) is a nonlinear and nonstationary signal obtained from electrodes attached on the skin surface of muscles [8].…”
Section: Introductionmentioning
confidence: 99%